External Jugular Vein Aneurysm in a Child With Hemophilia A. Issue 4 (June 2019) - Lee, Dong Hoon; Baek, Hee Jo; Yoon, Tae Mi; Lee, Joon Kyoo; Lim, Sang Chul
Abstract : Abstract: An external jugular vein (EJV) aneurysm is an extremely rare disease. Ultrasonography with color doppler methods is considered the criterion standard for diagnosis of a venous aneurysm. The treatment of choice for an EJV aneurysm is surgical excision. Herein, we report an unusual case of an EJV aneurysm in a child with hemophilia A. Because the incidence of an EJV aneurysm is low, it is important to distinguish it from other neck lesions, including congenital disease. In addition, it should be noted that in hemophilia patients, an EJV aneurysm may occur in a spontaneous or small trauma.